CITIZEN JOURNALISM AND THE TRANSFORMATION OF CIVIC ENGAGEMENT PRACTICES IN THE POLITICAL SPACE ON SOCIAL MEDIA - Zulfa Ajda Khoiriyah; Karim Suryadi; Dede Iswandi; Sapriya (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The development of digital technology and social media has transformed patterns of political participation and citizen interaction in the public sphere. One important phenomenon in this context is the emergence of citizen journalism, which enables citizens to play an active role in the production and distribution of public information. This study aims to analyze the relationship between the practice of citizen journalism, civic engagement, and political dynamics on social media among Industrial Engineering students at Pasundan University. The study uses a quantitative approach with a correlational method. Data were collected through a five-point Likert scale questionnaire from 85 respondents selected using purposive sampling. Data analysis was conducted through validity, reliability, and Pearson correlation tests. The results show that citizen journalism has a positive and very strong relationship with political civic engagement (r = 0.818; p < 0.001). In addition, civic engagement also correlates positively and strongly with political dynamics on social media (r = 0.724; p < 0.001), and citizen journalism is positively related to political dynamics on social media (r = 0.629; p < 0.001). These findings indicate that student involvement in citizen journalism practices and digital citizenship activities plays an important role in shaping a dynamic digital political space. This study emphasizes the importance of strengthening digital literacy and citizenship awareness in supporting the quality of democracy in the digital age.